2014
DOI: 10.3748/wjg.v20.i22.6939
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary tumor of the pancreas in male patients: Report of 16 cases

Abstract: Male patients with SPT of the pancreas are older than female patients. There are no significant differences between male and female patients regarding surgical strategies and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 0 publications
6
46
0
1
Order By: Relevance
“…The most frequent symptoms in our series were abdominal pain or discomfort, followed by abdominal mass; 2 patients were asymptomatic. These findings are well in accordance with previous reports [79]. Preoperative diagnosis of SPTs is generally made by CT or MRI imaging.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most frequent symptoms in our series were abdominal pain or discomfort, followed by abdominal mass; 2 patients were asymptomatic. These findings are well in accordance with previous reports [79]. Preoperative diagnosis of SPTs is generally made by CT or MRI imaging.…”
Section: Discussionsupporting
confidence: 92%
“…Machado et al [6] observed that SPTs in male patients were more aggressive than those in female patients, and they should be managed more radically. On the contrary, Cai et al [7]. collected 16 male patients with SPTs, and observed that males were older than female patients and had a favorable outcome after surgery, with no recurrence or death of disease in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although less common than in females, male patients with SPN are recognized. Aggressive behavior of SPNs, both histologically and clinically, in male patients has been reported previously in some studies and reviews, although another study did not arrive at the same conclusion . None of these studies comparing male with female patients analyzed either CTNNB1 or APC genes for variants, although Machado et al found somatic KRAS variants in a male patient …”
Section: Discussionmentioning
confidence: 85%
“…Aggressive behavior of SPNs, both histologically and clinically, in male patients has been reported previously in some studies and reviews, 36,37 although another study did not arrive at the same conclusion. 38 None of these studies comparing male with female patients analyzed either CTNNB1 or APC genes for variants, although Machado et al found somatic KRAS variants in a male patient. 36 One of the six tumors in our study does not harbor detectable variants in CTNNB1, APC or any of the 50 genes tested, despite having nuclear beta-catenin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Solid pseudopapillary tumor (SPT) is considered as a rare pathological entity of the pancreas in children that generally has a low malignant potential . A complete surgical resection can achieve a favorable prognosis.…”
Section: Introductionmentioning
confidence: 99%